(untitled) (Scientific journal of the Fergana State University, 2024)
This small study describes factors in the development of national communicative competence and the scientific research of scientists associated with this area. The main purpose of the article is to analyze the views and opinions of world scientists regarding the formation of national communicative competence in linguistics. In this work, comparison and contrast methods were used, as a result, examples of research by scientists who conducted research from the historical development of communication to the present day are given. Instead of a final word, we present our own opinion while studying the research of world scientists.